PENGARUH METODE EDUTAINMENT TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS VII DI MTs NEGERI 4 LEBAK - Trikawati; Euis Ismayati Yuniar; Nurjaman; Lia Nurliana; Agung Budiyanto (Al-Mudarris, 2026)
This study examined the effect of the edutainment method on improving Indonesian language learning outcomes among seventh-grade students at MTs Negeri 4 Lebak. The edutainment method combines educational and entertainment elements to create an engaging learning environment and increase students’ participation in classroom activities. This research employed a quantitative approach using a Two-Group Pretest–Posttest Design involving an experimental class and a control class. Learning achievement tests were administered before and after the intervention to measure students’ learning outcomes. The findings revealed that both groups showed improvement; however, the experimental class demonstrated significantly higher gains than the control class. The average score of the control class increased from 60.12 to 73.42, whereas the experimental class improved from 60.42 to 89.54. These results indicate that the edutainment method contributed more effectively to enhancing students’ achievement in Indonesian language learning. Statistical analysis further confirmed a significant difference between the two groups, with a t-value of 18.34 and a p-value of 9.33 × 10⁻²³ (p < 0.05). This suggests that the application of the edutainment method had a positive and significant impact on students’ learning outcomes compared with conventional teaching methods. Therefore, the edutainment method can be considered an effective instructional strategy for improving Indonesian language learning outcomes and promoting active student engagement in Islamic secondary education settings.